(untitled) (Journal of Applied Learning and Teaching, 2023)
A substantial part of sustainability management education is teaching students how to deal with increasingly uncertain futures. Increasingly, academics concerned with sustainability challenges claim that a sustainable way of being with the world needs a transformational shift in how humans relate to one another and the natural world. This paper takes this as a starting point to show the potentials of a relational approach to future scenario planning for developing an ecopedagogy of strategic sustainability management education. For this, it describes a course design that uses narratives to sensitise students to the contingent and composed nature of reality and enable them to take part in negotiating and shaping current and future realities together with others. The paper then highlights the importance of aesthetics for developing transformational capacities. It closes with a reflection on the limits of relational course designs in cultural settings dominated by individuality, nature/culture divide and anthropocentrism.